The parallelization of Charlie's method on linear heat conduction equation using homogeneous cluster computing - 519824 Halijah Osman; Norma Alias; Baharom Sanugi; National Symposium Mathematical Sciences (12th : 2004 : International Islamic University Malaysia) (Skudai : Universiti Teknologi Malaysia, 2004)
41